Adhesion Behaviors of Abalone Under the Action of Water Flow - Zhang, Yun; Li, Shanpeng; Zuo, Pingcheng; Xu, Xiangling; Li, Jing; Liu, Jianlin (Frontiers in Mechanical Engineering, 2021)
The abalone is well known as a non-permanent adhesive organism, and its adhesion mechanism is beneficial to such areas as underwater robotics, high precision sensors, and intelligent devices. Firstly, we observe the posture response of an abalone under the action of different water flow conditions. The result shows that under a high velocity of water, it tends to make its tail comply with the water flow, and vice versa, under a low speed, its head tends to comply with the water flow. The finite element method (FEM) simulation is performed to display the stress field, which can reasonably explain this phenomenon, and the strength check is also made on the pedal and shell. Next, the critical velocity of water flow when the abalone is peeled from the substrate is calculated, where the CEL (Coupled Eulerian-Lagrangian) method is used in simulation. At last, the adhesion behaviors of an abalone located in a trough or when it is behind an obstacle are explored. Most of these findings can be supported by the experimental results. This analysis is helpful to make a deep understanding on the adhesion behaviors of marine creatures.